Zarządzanie karierą globalną - perspektywa organizacyjna - Miś, Alicja (Global career management - organizational perspective, 2006)
The presented article focuses on the globalization of career systems. It starts with the individual perspective, identifying individual characteristic of global career and then, moving to the organizational perspective, the article addresses two aspects of global career systems. The first describes the implications for Human Resource Management and career management in multinational corporations (including main problems of personal function: recruitment, development, motivation, employee relations). The second area is expatriation and repatriation of individuals as a part of their careers. This part of the article presents three theoretical models for understanding expatriation and repatriation from the organizational perspective (Perlmutter, Bartlett and Ghoshal, Altman and Baruch). The end of the article stresses the importance of reverse culture shock.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 99-108